Prescribing antibiotics in diabetic foot infection: what is the role of initial microscopy and culture of tissue samples?*. Issue 4 (3rd October 2016) - Chisman, Robin; Lowry, Danielle; Saeed, Mujahid A; Tiwari, Alok; David, Miruna D
Abstract: The aim of this study was to evaluate the role of microscopy, Gram stain and the culture of tissue samples in the antibiotic treatment of patients with diabetic foot infection. A retrospective review of patients with a diabetic foot infection was undertaken. Data analysed included the severity of infection, antibiotic prescribing patterns, microscopy and culture results. A total of 71 patients were included, from whom 114 tissue samples were collected. Gram stain results were in agreement with final culture results in 45·8% ( n  = 54) of samples. Overall sensitivity and specificity of the Gram stains were low (74·5% and 69·8%, respectively), although the specificity for Gram‐negative rods was high (98·5%). The presence or absence of 'pus cells' on microscopy was a poor predictor of culture results. Empirical prescribing of antibiotics was in accordance with local policy in 31·1% of patients, improving to 86·8 % following culture results. Microscopy, a skilled laboratory procedure, was generally a poor predictor of tissue culture results. However, the presence of Gram‐negative rods was suggestive of isolation in the culture of such organisms and could allow the early broadening of antibiotic treatment. Despite initial poor compliance of empirical antibiotic treatment regimens, prescribing was adjusted in light of culture results, suggesting these were important for clinicians.